Nicotinamide Riboside Supplementation Attenuates Obesity-Induced Adipose Tissue Fibrosis and Inflammation in Female Mouse Model. (14th June 2022) - Kim, Mi-Bo; Pham, Tho X; VanLuling, Molly; Kostour, Victoria; Kang, Hyunju; Corvino, Olivia; Jang, Hyungryun; Odell, William; Park, Young-Ki; Lee, Ji-Young
Abstract: Objectives: Nicotinamide riboside (NR) is a nicotinamide adenine dinucleotide (NAD+) precursor. We previously reported that in male diet-induced obesity mice, NR supplementation attenuated liver fibrosis by inhibiting the activation of hepatic stellate cells. However, whether NR elicits a similar effect in females has not been studied. Therefore, in this study, we investigated whether NR consumption can prevent the development of inflammation and fibrosis and improve NAD + metabolism in the liver and white adipose tissue (WAT) in female mice with diet-induced obesity Methods: Female C57BL/6J mice were fed a high-fat/high-sucrose/high-cholesterol control (HF), or a HF diet supplemented with NR (HF-NR; 400 mg/kg/day) for 20 weeks. The effects of NR on fibrosis and inflammation were assessed by biochemical, molecular, and histological analyses in the liver and gonadal WAT (gWAT). Metabolic rates, energy expenditure, and physical activity of mice were analyzed using indirect calorimetry. Results: The body weight of mice fed HF-NR was significantly lower than HF. Also, HF-NR showed reductions in fat mass, glucose intolerance, and serum cholesterol levels compared with HF. In the liver, NAD + content tended toward an increase in the HF-NR, but NR supplementation did not significantly alter liver steatosis and fibrosis, along with no changes in serum alanine aminotransferase levels. In gWAT, the HF-NR group displayed decreased weight and adipocyte size compared with HF. In addition, the numbers of crown-like structures, a marker of inflammation, were markedly reduced in the gWAT of HF-NR compared to the HF. Consistently, NR supplementation decreased the expression of macrophage and proinflammatory M1 macrophage markers. Mice fed HF-NR also exhibited decreased gWAT fibrosis, evidenced by less fibrogenic gene expression and collagen accumulation than HF. Metabolic rates, physical activity, and energy expenditure were significantly higher in the HF-NR group than in HF. Conclusions: NR supplementation increased metabolic rates, energy expenditure, and physical activity, preventing obesity and its-associated inflammation and fibrosis in the WAT of female mice. The data suggest that NR may have sex-dependent effects on tissue-specific inhibition of obesity-induced inflammation and fibrosis. Funding Sources: This study was supported by NIH 3R01DK108254-04S1.